Quality control of polymer solar modules by lock-in thermography - Hoppe, Harald; Bachmann, Jonas; Muhsin, Burhan; Druee, Karl-Heinz; Riedel, Ingo; Gobsch, Gerhard; Buerhop-Lutz, Claudia; Brabec, Christoph; Dyakonov, Vladimir (Journal of Applied Physics, 2010)
We have characterized lateral imperfections of photovoltaic modules based on solution processed polymer-fullerene semiconductor blends by means of lock-in thermography (LIT). The active layer of the solar cell modules is based on the heterogeneous organic semiconductor system poly(3-hexylthiophene):phenyl-C -butyric acid methyl ester and the power conversion efficiency of the modules reached nearly 2% under irradiation of an AM 1.5 solar simulator. Applying highly sensitive LIT allowed us to detect several kinds of laterally distributed defects originating from imperfections in the respective functional layers as well as in the quality of encapsulation. We show that LIT is a powerful method for the quality control of large area polymer solar cells and modules, enabling fast feedback for optimization of production parameters. © 2010 American Institute of Physics.